Nursing Ethics in Risk Management - Ni Made, Ratih Comala Dewi; Ni Komang , Sri Wahyuni; I Made , Yudi Wahyu; Putu , Cintariasih; Kadek , Sri Wahyuni Dewi; Luh Gde , Nita Sri Wahyuningsih (Future Science, 2024)
Introduction: Hospitals are obliged to carry out health services that are quality, safe, effective, anti-discrimination, and always prioritize patient safety. Risk management is closely related to the implementation of patient safety in hospitals and has an impact on achieving hospital quality. From an ethical perspective, the value of trust is a prerequisite for success-ful risk management. This value is related to safety culture because it refers to physical safety, psychological safety, and cultural safety. The purpose of this writing is to find out and provide information about nursing ethics in risk management, especially related to patient safety.Methods: The method of free exploration and also the approach of journals, laws and regulations of the Ministry of Health of the Republic of Indonesia. The data sources used three journal databases: ScienceDirect, PubMed, and Google Scholar. Keywords in this literature review are adjust-ed to Medical Subject Heading (MeSH) which consists of “nursing ethics” AND “patient safety” AND “risk management”. Several inclusion criteria were set to obtain eligible articles: published between 2014 and 2024, and written in English or Bahasa. Result: This report presents an explanation of risk management related to patient safety. In the implementation of patient safety programs, one of them is the aspect of nursing ethics that is closely related to patient safety.Conclussion : Patient safety is multidimensional and is the ultimate goal of the healthcare system, which is to ensure the quality and safety of services, it is necessary to have structured policies and processes to pro-mote a shared safety environment.